The effect of the ex vivo addition of vitamin D on the prothrombotic and fibrinolytic potential in prostate cancer patients' blood. - Bester, Janette (University of Pretoria, 2022)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2022.